2013
DOI: 10.1007/s10147-013-0634-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of treatment outcomes based on tumor marker trends in patients with recurrent hepatocellular carcinoma undergoing trans-catheter arterial chemo-embolization

Abstract: The DCP trend might be useful for assessing treatment outcomes after TACE in patients with recurrent HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…The objective response rate using enhancement criteria ranges between 58 and 86%, and 20–41% achieve complete response [538, 541543]. In addition, the biological response based upon changes in tumor markers after treatment might be used as an ancillary method for assessment of overall response [544, 545]. …”
Section: Decisions On Resectability Of Hccmentioning
confidence: 99%
“…The objective response rate using enhancement criteria ranges between 58 and 86%, and 20–41% achieve complete response [538, 541543]. In addition, the biological response based upon changes in tumor markers after treatment might be used as an ancillary method for assessment of overall response [544, 545]. …”
Section: Decisions On Resectability Of Hccmentioning
confidence: 99%
“…For patients treated with sorafenib, an early decrease in serum AFP levels indicates a higher probability of response [ 11 ]. In HCC patients receiving transarterial chemoembolization (TACE), the response of AFP and PIVKA-II is positively associated with the radiological response [ 12 , 13 ]. However, the predictive role of AFP and PIVKA-II in HCC patients receiving anti-PD-1 therapy remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Serum alpha-fetoprotein (AFP) is the most widely used tumour marker in patients with HCC and has been proven to have capability of prefiguring the prognosis [29] and aid in monitoring for tumour recurrence [30]. Recently it has been shown that protein induced by vitamin K absence, antagonist-II (PIVKA-II), effectively increases the detection rate of HCC as a valid complement to AFP and imaging surveillance [31].…”
Section: Laboratory Findingsmentioning
confidence: 99%